Penambahan Madu Dalam Pengenceran Sperma Untuk Motilitas Spermatozoa, Fertilisasi dan Daya Tetas Telur Ikan Nila (Oreochromis niloticus) - Nainggolan, Ramses; Monijung, Revol D; Mingkid, Winda (Universitas Sam Ratulangi, 2015)
The research intends to determine the optimal concentration of honey addition in sperm dilution on sperm motility, fertilization and eggs hatchability of Nile Tolapia (Oreochromis niloticus). Experimental design used was a Complete Randomized Design (CRD) with three times repetition of four treatments. The concentration of honey addition used for treatment are A (0 ml of honey in 100 ml of physiological NaCl), B (0.60 ml of honey in 99.40 ml of physiological NaCl), C (0.65 ml of honey in 99.35 ml of physiological NaCl), D (0.70 ml of honey in 99.30 ml of physiological NaCl). Parent used consisted of five female parent and five male parent with 250 – 500 mg weight. Sperm dilution containers used was 12 plastic cups and the container fertilization and hatching eggs container used was 12 brass plates. Spermatozoa motility observation performed immediately after dilution process. Fertilization observation was performed after 12 hours of fertilization process, and Egg Hatchability observation was performed after 60 hours of fertilization. The observation results showed that the addition of honey in sperm dilution contributed significant effect on spermatozoa motility, fertilization and eggs hatchability of Nile Tolapia (Oreochromis niloticus). This observation showed that the addition of 0.70 ml of honey in a sperm dilution was the best treatment seen from the average percentage of spermatozoa motility (73,33 %), fertilization (80,00%) and eggs hatchability (77,33 %.) Keywords: Honey, sperm dilution, spermatozoa motility, fertilization, eggs hatchability Nile Tolapia